The role of antioxidant vitamins and enzymes in the prevention of exercise-induced muscle damage - Dekkers, J. C.; van Doornen, L. J.; Kemper, H. C. (Sports Medicine, 1996)
A growing amount of evidence indicates that free radicals play an important role as mediators of skeletal muscle damage and inflammation after strenuous exercise. It has been postulated that the generation of oxygen free radicals is increased during exercise as a result of increases in mitochondrial oxygen consumption and electron transport flux, inducing lipid peroxidation. The literature suggests that dietary antioxidants are able to detoxify the peroxides produced during exercise, which could otherwise result in lipid peroxidation, and that they are capable of scavenging peroxyl radicals and therefore may prevent muscle damage. Endogenous antioxidant enzymes also play a protective role in the process of lipid peroxidation. The studies reviewed (rodent and human) show significant increases of malondialdehyde (a product of lipid peroxidation) after exercise to exhaustion, and also favourable changes in plasma antioxidant levels and in antioxidant enzyme activity. In trained individuals and trained rats, the antioxidant enzyme activity increases markedly. In this way, the increased oxidative stress induced by exercise is compromised by increased antioxidant activity, preventing lipid peroxidation. Human studies have shown that dietary supplementation with antioxidant vitamins has favourable effects on lipid peroxidation after exercise. Although several points of discussion still exist, the question whether antioxidant vitamins and antioxidant enzymes play a protective role in exercise-induced muscle damage can be answered affirmatively. The human studies reviewed indicate that antioxidant vitamin supplementation can be recommended to individuals performing regular heavy exercise. Moreover, trained individuals have an advantage compared with untrained individuals, as training results in increased activity of several major antioxidant enzymes and overall antioxidant status. However, future studies are needed in order to be able to give more specific information and recommendations on this topic.